Phytochemical Tests and Antioxidant Activities of the Rhips Ginger (Zingiber Officinale Var Amarum.) - Hasanela, Nurani; Bandjar, Adriani; Yanyaan, Virenze K.; Hitijahubessy, Hendro (Indonesian Journal of Chemical Research, 2023)
Ginger is a traditional plant that thrives and has essential functions, including an antioxidant. This study aimed to determine the phytochemical content and test the antioxidant activity of fresh white ginger and powdered ginger (Zingiber officinale var. Amarum.). Two methods are used in this research: the phytochemical test and the antioxidant activity test using DPPH. Phytochemical tests, such as flavonoid, phenolic, steroid, and saponin, were conducted qualitatively. The antioxidant activity test was carried out using a UV-Vis spectrophotometer. Fresh white ginger and powdered ginger were extracted using the maceration method with water solvent. The study results showed that the effects of fresh white ginger extract obtained a yield of 64.08%. Meanwhile, powdered ginger extract was 58.68%. Phytochemical test results of fresh white ginger extract and powdered ginger (commercial) showed positive results for flavonoid, phenolic, and saponin compounds while adverse effects for steroids. Antioxidant activity test on fresh white ginger extract with water solvent showed an IC50 value of 25.41 ppm. The powdered ginger extract (commercial) has an IC50 value of 36.70 ppm. The results showed fresh white ginger and powdered ginger had relatively high antioxidant activity.